Survival protein A is essential for virulence in Yersinia pestis. (March 2016) - Southern, Stephanie J.; Scott, Andrew E.; Jenner, Dominic C.; Ireland, Philip M.; Norville, Isobel H.; Sarkar-Tyson, Mitali
Abstract: Plague is a highly pathogenic disease caused by the bacterium Yersinia pestis . There is currently no vaccine available for prophylaxis and antibiotic resistant strains have been isolated, thus there is a need for the development of new countermeasures to treat this disease. Survival protein A (SurA) is a chaperone that has been linked to virulence in several species of bacteria, including the close relative Yersinia pseudotuberculosis . In this study, we aimed to evaluate the role of SurA in virulence of the highly pathogenic Y. pestis by creating an unmarked surA deletion mutant. The Y. pestis Δ surA mutant was found to be more susceptible to membrane perturbing agents and was completely avirulent in a mouse infection model when delivered up to 2.1 × 10 5 CFU by the subcutaneous route. This provides strong evidence that SurA would make a promising antimicrobial target. Highlights: This study evaluates the role of SurA in Yersinia pestis. Deletion of the surA gene has an effect on the cell envelope. A surA mutant is avirulent in a Y. pestis mouse infection model.